AI4SE and SE4AI: A Research Roadmap. Issue 1 (15th April 2020) - McDermott, Tom; DeLaurentis, Dan; Beling, Peter; Blackburn, Mark; Bone, Mary
ABSTRACT: In 2019, the Research Council of the Systems Engineering Research Center (SERC), a US Defense Department sponsored University Affiliated Research Center (UARC), developed a roadmap structuring and guiding artificial intelligence (AI) and autonomy research. This paper presents that roadmap and key underlying Digital Engineering transformation aspects both enabling traditional systems engineering practice automation (AI4SE), and encourage new systems engineering practices supporting a new wave of automated, adaptive, and learning systems (SE4AI).